Derecho al buen vivir y la inseguridad ciudadana en el cantón Guaranda en el año 2021. - Aguirre Aucatoma, José Andrés (2023)
Procedural speed as a constitutional norm is a principle that must be applied by the courts, so that all criminals who must be evacuated in a judicial dispute are quickly and effectively. Our constitution of Ecuador determines the principle of celerity, the same that must be expeditious and effective, we must analyze if this principle is fully complied with and be able to verify if its application, today to the high percentage of criminals, has led to justice is subject to these groups, leaving procedural speed as a utopia. Currently, with the implementation of the principles of immediacy and concentration, the aim is to improve the administration of justice. The Ecuadorian legal system establishes effective judicial protection as a right of protection of the Ecuadorian state for citizens, however a flawed judicial system is observed with procedures without the proper application of effective protection since the accused are released as quickly as possible. possible, that is, once they are arrested and placed under the prosecutor's orders for the lack of formulation of charges or misapplication of the people who intervene in the trials, they injure the rights of those who need to go to the judicial bodies in search of effective judicial protection. to solve the inconveniences that arise according to the case. It is ironic to go to justice in search of it, and find the opposite, a flawed judicial system that does not facilitate the application of constitutional principles and the guarantee of legal certainty. Keywords: citizen insecurity, poverty, crime, public policies, speed